2016
DOI: 10.7314/apjcp.2015.16.18.8487
|View full text |Cite
|
Sign up to set email alerts
|

Improved Detection of Helicobacter pylori Infection and Premalignant Gastric Mucosa Using "Site Specific Biopsy": a Randomized Control Clinical Trial

Abstract: Background: Helicobacter pylori infection and premalignant gastric mucosa can be reliably identified using conventional narrow band imaging (C-NBI) gastroscopy. The aim of our study was to compare standard biopsy with site specific biopsy for diagnosis of H. pylori infection and premalignant gastric mucosa in daily clinical practice. Materials and Methods: Of a total of 500 patients who underwent gastroscopy for investigation of dyspeptic symptoms, 250 patients underwent site specific biopsy using C-NBI (Group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 11 publications
(11 reference statements)
1
18
0
1
Order By: Relevance
“…The degree of correspondence between the two methods was 89.1% . Furthermore, NBI enables the sampling of targeted biopsies (“site specific”) vs standard site biopsies; this method was shown to be more effective for both detection of H. pylori and detection of premalignant lesions …”
Section: Invasive Testsmentioning
confidence: 97%
See 1 more Smart Citation
“…The degree of correspondence between the two methods was 89.1% . Furthermore, NBI enables the sampling of targeted biopsies (“site specific”) vs standard site biopsies; this method was shown to be more effective for both detection of H. pylori and detection of premalignant lesions …”
Section: Invasive Testsmentioning
confidence: 97%
“…7 Furthermore, NBI enables the sampling of targeted biopsies ("site specific") vs standard site biopsies; this method was shown to be more effective for both detection of H. pylori and detection of premalignant lesions. 8 Confocal laser endomicroscopy allows a microscopic visualization of the mucosa during endoscopy at an approximately 1000-fold magnification which results in an optimized diagnosis of gastric atrophy and intestinal metaplasia as well as limiting the sampling error of untargeted biopsies. 9 While more useful for the esophagus, it can be used for grading premalignant lesions of the stomach with even higher accuracy than NBI or chromoendoscopy.…”
Section: Endoscopymentioning
confidence: 99%
“…Written informed consent was obtained from all patients, and the study protocol was approved by the Ethics Committee for Research Involving Human Subjects, Suranaree University of Technology (EC-59-45 and EC 16-2560). e whole stomach was examined and biopsies were conducted using the site-specific biopsy technique [40]. All biopsies were directly tested for H. pylori infection by using the rapid urease test (RUT) kit (Pentland Medical, Edinburgh, UK).…”
Section: Patients and Specimensmentioning
confidence: 99%
“…On a similar note, Tongtawee et al 's38 study of 200 patients demonstrated that NBI also reliably identifies gastric mucosal morphological patterns associated with H. pylori infection, which correlated significantly with severity of pathological inflammation grading. A subsequent randomised study39 on 500 subjects noted site-specific biopsy guided by NBI had higher yield of diagnosing Helicobacter , as compared with standard WLE biopsy. Findings by Ang and Tongtawee suggest that NBI would be useful to identify sites for high-yield targeted biopsies.…”
Section: Flexible Spectral Imaging Colour Enhancement (Fice)mentioning
confidence: 98%